THE DEVELOPMENT OF BUSINESS ECONOMICS TEACHING MATERIALS BASED ON PROJECT BASED LEARNING (PJBL) VOCATIONAL SCHOOL STUDENTS - Lilik Sri Hariani; Endah Andayani; Nurul Ain (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
This study aims to develop teaching materials for business economics based on Project Based Learning (PjBL) for vocational high school students with materials for small and medium business plans. The development of the model uses an R&D approach in the field of Education (Bord and Gall) which has been modified as proposed by Sugiono with 3 (three) steps; 1) preliminary study, 2) model development. And 3) model testing. Based on the results of testing the model related to the feasibility assessment of the validators consisting of material expert validators and linguist validators, the results obtained that the product development was very feasible to be used in the teaching and learning process. Besides that, the results of the effectiveness assessment in the form of responses from teachers and student responses through questionnaires can be obtained that the product developed is very feasible to use. These results indicate that business economics teaching materials developed based on PjBL on small and medium business plan materials are feasible to use in the teaching and learning process.